2013
DOI: 10.1039/c2dt31775c
|View full text |Cite
|
Sign up to set email alerts
|

Random nanowires of nickel doped TiO2with high surface area and electron mobility for high efficiency dye-sensitized solar cells

Abstract: Mesoporous TiO(2) with a large specific surface area (~150 m(2) g(-1)) is the most successful material in dye-sensitized solar cells so far; however, its inferior charge mobility is a major efficiency limiter. This paper demonstrates that random nanowires of Ni-doped TiO(2) (Ni:TiO(2)) have a dramatic influence on the particulate and charge transport properties. Nanowires (dia ~60 nm) of Ni:TiO(2) with a specific surface area of ~80 m(2) g(-1) were developed by an electrospinning technique. The band gap of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 55 publications
(62 reference statements)
0
31
0
Order By: Relevance
“…Rationale of using electrospun nanowires is that they can support high electron diffusivity and mobility, which would enhance the charge collection efficiency, and can be tailored by controlling the crystallinity. [32][33][34][35][36] The devices that employed electrospun ZnO nanowires gave up to ~20% higher PCE than control devices that did not employ them. The enhanced PCE resulted from an increase in the fill factor; and therefore, the electrospun ZnO nanowires reduce the charge recombination rate and improve the collection efficiency.…”
Section: Introductionmentioning
confidence: 96%
“…Rationale of using electrospun nanowires is that they can support high electron diffusivity and mobility, which would enhance the charge collection efficiency, and can be tailored by controlling the crystallinity. [32][33][34][35][36] The devices that employed electrospun ZnO nanowires gave up to ~20% higher PCE than control devices that did not employ them. The enhanced PCE resulted from an increase in the fill factor; and therefore, the electrospun ZnO nanowires reduce the charge recombination rate and improve the collection efficiency.…”
Section: Introductionmentioning
confidence: 96%
“…5,14 On the other hand, p-type dopants such as Ni, although lowered the Fermi level of TiO 2 , increased the crystallinity and improved the D n through it. 13 The mechanism of such improvement in D n through increase in crystallinity is from lowering of density of localized energy states occur in the band gap, the occurrence of which is the root cause of poor D n in nanomaterials. 20,21 Although a number of studies have reported that details improved PV performance in Zr doped TiO 2 (Zr:TiO 2 ), 12,22 the mechanism of such improvement is still unclear.…”
mentioning
confidence: 99%
“…This definitely declines the photo activity of Ni/anatase under UV light, albeit the defect states prompt it under the visible light. However, some experimental results reported the more photo-efficiency of Ni/TO 2 than pure TiO 2 under UV condition [11,37]. It may refer to the difference between the crystalline structure of that Ni/TiO 2 and our calculated case such as, the presence of some defect in the bulk e.g.…”
Section: Electronic Structurementioning
confidence: 90%